2012
DOI: 10.1371/journal.pone.0047299
|View full text |Cite
|
Sign up to set email alerts
|

Activating Nrf-2 Signaling Depresses Unilateral Ureteral Obstruction-Evoked Mitochondrial Stress-Related Autophagy, Apoptosis and Pyroptosis in Kidney

Abstract: Exacerbated oxidative stress and inflammation may induce three types of programmed cell death, autophagy, apoptosis and pyroptosis in unilateral ureteral obstruction (UUO) kidney. Sulforaphane activating NF-E2-related nuclear factor erythroid-2 (Nrf-2) signaling may ameliorate UUO-induced renal damage. UUO was induced in the left kidney of female Wistar rats. The level of renal blood flow, cortical and medullary oxygen tension and reactive oxygen species (ROS) was evaluated. Fibrosis, ED-1 (macrophage/monocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 46 publications
5
136
0
Order By: Relevance
“…Furthermore, Kida et al and Sato et al determined that a positive linear relationship exists between tubular dilatation and tubular epithelial apoptosis in UUO mice (18). Increased ROS, lipid peroxidation, and compromised antioxidants were previously found in a number of studies using obstructed rodent kidneys (6,24,35,48), and ROS have been suggested to impair the integrity of the glomerular basement membrane, reduce podocyte proteoglycan de novo synthesis, and stimulate factors promoting ECM deposition, including TGF-␤ 1 (9), as similarly observed in the present study. Overall, these results corroborate our results in the RTEC model system.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, Kida et al and Sato et al determined that a positive linear relationship exists between tubular dilatation and tubular epithelial apoptosis in UUO mice (18). Increased ROS, lipid peroxidation, and compromised antioxidants were previously found in a number of studies using obstructed rodent kidneys (6,24,35,48), and ROS have been suggested to impair the integrity of the glomerular basement membrane, reduce podocyte proteoglycan de novo synthesis, and stimulate factors promoting ECM deposition, including TGF-␤ 1 (9), as similarly observed in the present study. Overall, these results corroborate our results in the RTEC model system.…”
Section: Discussionsupporting
confidence: 87%
“…As a transcription factor, Nrf2 can regulate the expression of autophagy adaptor protein NDP52 and p62/SQSTM1, presumably facilitating autophagy (51,52). However, knocking down Nrf2 resulted in an increase of autophagy, suggesting a suppressive role of Nrf2 in autophagy (53)(54)(55). Although suppression of mitophagy may contribute to an inhibition of mitochondrial loss, a deficit in mitophagy results in the accumulation of dysfunctional mitochondria characterized by mitochondrial swelling, loss of cristae structure, decreased membrane potential, and decreased capacity for metabolism (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…[144][145][146][147] The unique feature of pyroptosis compared with other pathways of regulated necrosis is the maturation of proinflammatory cytokines during the cell death process, [148][149][150] which depends on cleavage mediated by nonapoptotic caspases. Many of the in vivo studies on pyroptosis have been performed in caspase 1-deficient mice, which have been described to carry a passenger mutation that functionally renders them caspase 1/11 double-deficient.…”
Section: Pyroptosis-maximal Immunogenicity Of Necrosismentioning
confidence: 99%